The Waithood Generation: an African perspective about youth’s strategies in the contemporary world - Carvalho, X. (Research in Education, 2014)
Come gather ’round people Wherever you roam And admit that the waters Around you have grown And accept it that soon You’ll be drenched to the bone If your time to you is worth savin’ Then you better start swimmin’ or you’ll sink like a stone For the times they are a-changin’ (Excerpt of Bob Dylan’ song The Times They Are a-Changin’, 1963) Alcinda Honwana begins her book The Time of the Youth: Work, Social Change and Politics in Africa (2012) invoking Bob Dylan’s song The Times They Are a-Changin’ (1963). From 1968 in Europe to the riots in the UK in 2011 and the Arab Spring in 2010, Honwana draws the portrait of contemporary youth and the feeling of discontent all around the world in a neo-liberal economical and political landscape. No matter if it is a poor or a rich country, in the South or in the North, youth is sharing the same expectations and it is creating new strategies for understanding and overcoming an age of youth’ marginalization linked with access to education, employment and social construction of their own adulthood. In the modern capitalist society, as Honwana argues, youth as been the space of cultural reproduction and social self-awareness through education, a space where society ‘hides its dreams’ – Honwana’s invocation of Foucault’s words of 1976. If indeed youth, in the industrialized countries, is a transition stage from education to work, there is a need to re-conceptualize the notion of youth itself, considering it a social category much more than a matter of age classification. However, this marginalization process seems to be more profound in Africa, as Honwana argues, in spite of the fact that this is a globalized trend. So the author draws on African youth and their expectations regarding the present and future times that are a-Changin’, presenting the African youth’s own narratives.